Timing and cell dose determine therapeutic effects of bone marrow stromal cell transplantation in rat model of cerebral infarct. Issue 2 (21st June 2012) - Kawabori, Masahito; Kuroda, Satoshi; Ito, Masaki; Shichinohe, Hideo; Houkin, Kiyohiro; Kuge, Yuji; Tamaki, Nagara
<x xml:space="preserve">Abstract</x> Stereotactic transplantation of bone marrow stromal cells (BMSCs) enables efficient delivery to the infarct brain. This study was aimed to assess its optimal timing and cell dose for ischemic stroke. The BMSCs were harvested from the green fluorescent protein‐transgenic rats and were labeled with quantum dots. The BMSCs (1 × 105 or 1 × 106) were stereotactically transplanted into the ipsilateral striatum of the rats subjected to permanent middle cerebral artery occlusion at 1 or 4 weeks post‐ischemia. Motor function was serially assessed. Using in vivo near infrared (NIR) fluorescence imaging, the engrafted BMSCs were visualized at 3 weeks post‐transplantation. Immunohistochemistry was performed to evaluate their fate. Functional recovery was significantly enhanced when both low and high doses of BMSCs were transplanted at 1 week post‐ischemia, but such therapeutic effects were observed only when the high‐dose BMSCs were transplanted at 4 weeks post‐ischemia. Both optical imaging and immunohistochemistry revealed their better engraftment in the peri‐infarct area when the high‐dose BMSCs were transplanted at 1 or 4 weeks post‐ischemia. These findings strongly suggest the importance of timing and cell dose to yield therapeutic effects of BMSC transplantation for ischemic stroke. Earlier transplantation requires a smaller number of donor cells for beneficial effects.